The Effect of Cyclic Bending Loads on Crack Growth in Pipes for Inclined and Transverse Cracks with or Without Internal Pulsing Pressure - Fathi Alshamma; Shwan Abdulmuhsin Zainalaabdeen (Journal of Engineering, 2017)
In the present research a new test rig has been proposed to be suitable for different cyclic loads such as cyclic bending, cyclic torsion, proportional and non proportional loads. In this work the efforts were concentrated on the cyclic bending loads concerning cracked pipes with or without internal pulsing pressure to study crack propagation in small bore pipes (up to 1'') for transverse or inclined cracks. The rig simulates the real service conditions under different stresses by means the least dangerous case will be suggested, so the experiments were considered for copper pipe, and the results have been tabulated and drawn to demonstrate the crack growth behavior as well as to justify the outcomes practically, consequently the durability of this new rig has been confirmed with new concluded facts.